Development and characterization of silica supported cobalt oxides for ethanol oxidation using different preparation methods. (June 2020) - Osakoo, N.; Khemthong, P.; Roessner, F.; Kidkhunthod, P.; Chanlek, N.; Prayoonpokarach, S.; Wittayakun, J.
Abstract: Cobalt oxide in spinel structure (Co3 O4 ) is an efficient catalyst for ethanol oxidation due to its potential as an oxygen source. To enhance the catalytic performance, Co3 O4 is dispersed on silica (SiO2 ). The degree of dispersion and form of oxides on the support depend on the preparation method. The objective of this work is to compare physicochemical properties and catalytic performance in ethanol oxidation of silica-supported cobalt catalysts from different preparation methods. The catalysts were prepared by incipient wetness impregnation (IP), precipitation with reverse micelle (RM), and precipitation with NH4 OH (PN) methods. The forms and dispersion of cobalt species were investigated by X-ray absorption near edge structure (XANES), extended X-ray absorption fine structure (EXAFS) and X-ray photoelectron spectroscopy (XPS). The cobalt species from RM and IP methods were mainly Co3 O4, but that from PN method was the mixed phases of Co3 O4, CoO and Co2 SiO4 . The RM method provided the best dispersion of Co3 O4, surface Co 3+ and lattice O 2− on SiO2 . Consequently, the catalyst from RM method provided the highest ethanol conversion and CO2 yield from all temperature ranges. Graphical abstract: Image 1 Highlights: Cobalt oxides supported on silica as catalysts were prepared by three methods. Forms of cobalt were studied by X-ray absorption and photoelectron spectroscopies. Reverse micelle and impregnation gave mainly Co3 O4 but not for precipitation by NH4 OH. The reverse micelle method provided the best dispersion of Co3 O4 on SiO2 . The reverse micelle method had the highest ethanol conversion and CO2 yield.